2018
DOI: 10.3390/molecules23040819
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phenolic Acids from the Rhizosphere Soils of Panax notoginseng as a Double-Edge Sword in the Occurrence of Root-Rot Disease

Abstract: Chemical agents in the rhizosphere soils of plants might have an influence on root-rot disease, which therefore might reveal the mechanism of root rot in Panax notoginseng (P. notoginseng). With this hypothesis the alterations of phenolic acids (PAs) in the rhizosphere soils of P. notoginseng after pathogen infection were determined. The effects of PAs on the growth of Fusarium oxysporum (F. oxysporum), a fungal pathogenic factor for P. notoginseng, as well as production of fusaric acid, a wilting agent for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 30 publications
(25 reference statements)
1
23
0
Order By: Relevance
“…The influence of vanillic acid and rutin, showing either slight growth inhibition or increase depending on the substance and fungal species remains undisclosed and needs to be investigated in more detail. So far, the effects of these substances were mainly tested against soil-borne Fusarium species such as F. oxysporum (Mohamed et al 2017;Zhao et al 2018) and F. solani (Kalinova and Radova 2009). Both phenolic compounds were able to reduce growth of these fungal species, however, an increase of fusaric acid was also reported.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of vanillic acid and rutin, showing either slight growth inhibition or increase depending on the substance and fungal species remains undisclosed and needs to be investigated in more detail. So far, the effects of these substances were mainly tested against soil-borne Fusarium species such as F. oxysporum (Mohamed et al 2017;Zhao et al 2018) and F. solani (Kalinova and Radova 2009). Both phenolic compounds were able to reduce growth of these fungal species, however, an increase of fusaric acid was also reported.…”
Section: Discussionmentioning
confidence: 99%
“…community abundance. An in vitro experiment showed that the growth of Fusarium species is inhibited by the presence of high VA concentrations ( Samapundo et al, 2007 ; Zhao et al, 2018 ). Previous studies usually applied high concentrations of active phenolic acids that might not be relevant to the actual field conditions ( Inderjit and Bhowmik, 2004 ; Inderjit et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…were found in the endophytic bacterial community of the roots in the treated plant samples [ 9 ]. Moreover, phenolic acids can affect soil-borne pathogen growth [ 10 , 11 ]; for example, R. solanacearum can utilize salicylic acid (inducement of host defense response) to stimulate its growth and enhance its virulence in tomato plants [ 11 ]. Ferulic acid is a novel inducer of the type 3 secretion system (T3SS) in R. solanacearum , which can promote the R. solanacearum infection process in tomato plants [ 12 ].…”
Section: Introductionmentioning
confidence: 99%